RETRACTED: Training of teachers for teaching in the conditions of distance education - Yekimov Sergey; Salkova Daniela; Sharov Sergii; Belotserkovskaya Nataliya; Oleksenko Roman; Kompanets Eduard (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001